O céu riscado na pele : uma poética do deslocamento - Pires, Andréia Alves (2017)
This work presents the unpublished novel O Céu riscado na pele and the theoretical-critical reflection that accompanies it. What is a woman made of? Who comes first: the mother or the daughter? These are intimate conflicts that Lúcia, the protagonist, wants to solve while dealing with her own experience of motherhood. Narrative that has by impulse the movement of the feminine and that founds in itself a microcosm of cultural mobility based on displacement, O céu riscado na pele is a history of women told by women, on the ways in which a woman understands herself as subject in its world from certain conditions of existence and in complex and deep relation with the women who preceded and will eventually succeed. The study on the narrative course carried out discusses the theoretical problem of displacement and the relations with the topic of motherhood, develops thematic, compositional and enunciative conceptions that guided the writing of the fictional text and demonstrates the creative process of the novel, proposing a singular poetics of the authorial displacement.